Fitorremediação do glifosato utilizando o capim marandu - André, Rita de Cássia (2020)
The use of herbicides has contributed to weed control in crops, with glyphosate being one of the most widely used herbicides in Brazil. The phytoremediation technique has the ability to remedy soil herbicides. The work evaluated the effect of simulated rain on the cultivation of brachiaria (Urochloa brizantha), for phytoremediation of the herbicide glyphosate in Oxisol of the Cerrado, using soybeans (Glycine max L.) as a bioindicator plant. The experimental design was in randomized blocks in a 5x3 factorial scheme, with five periods of application of the herbicide before sowing (0, 3, 6, 9 and 12 days) and three regimes of simulated rain (0, 20 and 30 mm), resulting in in 60 experimental plots. The variables of emergency speed index (IVE), percentage of emergency (%), chlorophyll SPAD index, visual phytointoxication (%) were evaluated at 17, 24 and 30 days after sowing of U. brizantha and at 3, 16 and 23 days after sowing of G. max, plant height (cm), fresh weight (g) and dry weight (g) of the aerial part and root. The results were subjected to analysis of variance, compared by quantitative regression analysis (P> 0.05). The interaction between the treatments caused variations in the two species in soil, with emergence speed index, percentage of emergence, plant height, fresh air weight, fresh root weight and dry root weight for U. brizantha and in the fresh weight variables air weight, dry root weight and SPAD chlorophyll index for G. max. The values obtained from the variables were higher with the increase of the rain blade and a more distant period between spraying and sowing, inversely the variable emergence speed index and percentage of emergence that obtained the highest value with a longer spraying and sowing period next. The U. Brizantha showed resistance to the herbicide glyphosate, however it did not completely remedy the effect of the herbicide in soil, as G. Max showed symptoms of phytointoxication.